REINTERPRETASI HADIST NABI TENTANG WANITA SEBAGAI SUMBER FITNAH PERSPEKTIF TEORI GENERATIF TRANSFORMATIF NOAM CHOMSKY - Mushab Wafi Adalah dan Muhammad Khoirul Anwar (al Dhikra | Jurnal Studi Qur'an dan Hadis, 2023)
The importance of understanding hadith in a complex way. Shows a dynamics of texts that have a spirit of benefit. This article aims to reinterpret a hadith which textually often legalizes the existence of women as a source of slander. This effort is important considering the position of hadith as the second resource in the foundation Islamic law. The authenticity and validity of hadith is very important to study, but understanding it with the right understanding is very important to know the purpose of a hadith editor. This study uses generative transformative pioneered by Noam Chomsky which emphasizes looking at the structure of language which is divided into two: first, deep structure or inner structure and secondly surface structure or outer structure. This article concludes that these two traditions have similarities but have different editorials, both in the form of expansion and permutation. Than As-Subki in interpreting women’s traditions is slander using a deep structure approach. Whereas Ibnu Hajar and Al-Qosthallani prefer to use a surface structure approach, and Al-Qordhowi prefer to use a deep structure and surface structure.